University of the Future and Forth Industrial Revolution. Towards an innovative University. Prospective Analysis (Revista Electrónica Calidad en la Educación Superior, 2020)
The rise of the digital transformation forces to renew the Higher Education; what is expected is to have a University of the future which implies to move from the model I+D Innovation + Development to the model I+D+ii Innovation + Development + Intelligent innovation; that is to say that the University will be conformed of human intelligence and artificial intelligence and that it is articulated from two components the intelligent curriculum that offers freedom in the formation and in the academic innovations and  the scientific and technological innovations.  The University must advance in accordance with the progress of society and offer its contribution to science and technology. The function of the University traditionally throughout history has been the formation of academic elites and the formation of specific groups for a labor market. However, the function of the University goes beyond the traditional nowadays as it is the contribution to the society through its researches that become contributions that influence in the productive development since the scarce link with the productive sector makes that the Universities work in an isolated way and that their academic functions as the researches become unimportant. Society in general demands a university that goes beyond the simple transmission of knowledge, but rather an institution that contributes to development through science and technology
Keywords: Higher Education; Industry 4.0; Innovation